Client and Contractor Organisations’ Assessment of Design-Bid-Build Procurement Practice in Nigeria - Dada, M.O. (Institute of Research and Community Outreach - Petra Christian University, 2013)
This study sought to investigate the assessment of client and contractor organizations on the use of the design-bid-build method for project delivery in Nigeria. One hundred fifty seven questionnaires were administered purposively on contracting and client organizations in Nigeria. Sixty seven organisations responded to the questionnaire. The responses were analysed through the use of descriptive and inferential statistical tools. Of the twenty issues used for the assessment, ‘individual participants are exploitative of loopholes in contract documents’ ranked first on aggregation for the two groups. ‘Relationships among participants breed mistrust’ ranked least. On the average, contractors and clients disagree with the twenty issues or criticisms about the traditional procurement practice. The results of the analysis further indicate that there are no significant differences in perceptions on the issues between the two groups. It is recommended that the homogeneity of perceptions can be a launching pad for further investigation and intervention efforts for procurement improvement in Nigeria.